Numerical analysis and experimental verification on flow characteristics of a pressurized fluidized bed system - YILMAZ, BARIŞ (My University, 2023)
© 2022 by ASME.The pressurized fluidized bed technology is recently shown to be a most promising technology for energy conversion and carbon capture. In the present work, two-phase flow characteristics of a laboratory-scale bubbling fluidized bed (BFB) system have been examined numerically under pressurized cold flow conditions. The BFB hydrodynamics is presented by axial pressure distributions and radial particle volume fractions. Moreover, the influence of drag models on minimum fluidization and bubble formation is studied using two different drag models, namely Wen-Yu/Ergun and EMMS-Yang, at both atmospheric and elevated pressure conditions. The numerical results are validated with a series of pressure drop and axial pressure measurements conducted at three different pressure conditions. The experimentally observed minimum fluidization velocity results are also compared with the theoretical correlations found in the literature. Good agreement has been found between experiments and numerical predictions.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Energy in Agriculture; Biofuels Technology; Geophysical Engineering; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Yerbilimleri; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; JEOKİMYA VE JEOFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; GEOSCIENCES; ENGINEERING, MECHANICAL; ENERGY & FUELS; GEOCHEMISTRY & GEOPHYSICS; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Yakıt Teknolojisi; Enerji Mühendisliği ve Güç Teknolojisi; Makine Mühendisliği; Jeokimya ve Petroloji; Renewable Energy, Sustainability and the Environment; Physical Sciences; Fuel Technology; Energy Engineering and Power Technology; Mechanical Engineering; Geochemistry and Petrology; bubbling fluidized bed; combustion of waste/fluidized bed; CPFD; drag models; energy conversion/systems; hydrodynamics; pressure; twophase